AZD6280, a Novel Partial γ-Aminobutyric Acid A Receptor Modulator, Demonstrates a Pharmacodynamically Selective Effect Profile in Healthy Male Volunteers. Issue 1 (February 2015) - Chen, Xia; Jacobs, Gabriel; de Kam, Marieke L.; Jaeger, Judith; Lappalainen, Jaakko; Maruff, Paul; Smith, Mark A.; Cross, Alan J.; Cohen, Adam; van Gerven, Joop
<x xml:space="preserve">Abstract</x> Objective AZD6280 is a novel γ-aminobutyric acid A receptor modulator with higher in vitro efficacy at the α2, 3 subtypes as compared to the α1 and α5 subtypes. This study compared the pharmacodynamic effects of single oral dose AZD6280 10 mg and 40 mg on the central nervous system with 2 mg of lorazepam. Methods Sixteen healthy males were enrolled into the double-blind, randomized, 4-way crossover study. Two validated central nervous system test batteries, Neurocart and CogState, were administered to measure drug effects on cognition, neurophysiologic function, and psychomotor and subjective feelings. Statistical analysis was performed using mixed model analysis of variance, with fixed factors of treatment, period, time and treatment by time, and random factors of subject, subject by treatment and subject by time, and the average prevalue as covariate. Results Most pharmacodynamic parameters were affected by lorazepam. AZD6280 induced dose-dependent smaller-than-lorazepam effects on saccadic peak velocity (SPV) (AZD6280, 10 mg vs. AZD6280, 40 mg vs. lorazepam [deg/s]: −22.6 vs. −50.0 vs. −62.9, P < 0.001), whereas the impacts on adaptive-tracking, body-sway, smooth-pursuit, and the one-card-learning tests were significant but much smaller than lorazepam. Thus, the slopes of regression lines for the ΔLog(Sway)-ΔSPV, ΔTracking-ΔSPV, and ΔSmooth-ΔSPV relations were flatter with AZD6280 than with lorazepam. AZD6280 caused a distinct electroencephalography signature from that of lorazepam. Conclusions The SPV responses to AZD6280 suggest potential concentration-related anxiolytic effects, whereas the smaller SPV-normalized effects of AZD6280 on various non-SPV pharmacodynamic parameters suggest a more favorable side effect profile compared to lorazepam. Overall, the pharmacodynamic profile of AZD6280 matches the pharmacological specificity and selectivity of this compound at the α2, 3 γ-aminobutyric acid A receptor subtypes.